Risk factors for postpartum relapse in women at risk of postpartum psychosis: The role of psychosocial stress and the biological stress system. (June 2021) - Hazelgrove, Katie; Biaggi, Alessandra; Waites, Freddie; Fuste, Montserrat; Osborne, Sarah; Conroy, Susan; Howard, Louise M.; Mehta, Mitul A.; Miele, Maddalena; Nikkheslat, Naghmeh; Seneviratne, Gertrude; Zunszain, Patricia A.; et al.
Abstract: Background: Postpartum psychosis is the most severe psychiatric disorder associated with childbirth, and the risk is particularly high for women with a history of bipolar disorder, schizoaffective disorder or those who have suffered a previous episode of postpartum psychosis. Whilst there is a lot of evidence linking stress to psychosis unrelated to childbirth, the role of stress in the onset of postpartum psychosis has not been fully investigated. Methods: A prospective longitudinal study of 112 pregnant women, 51 at risk of postpartum psychosis because of a DSM-IV diagnosis of bipolar disorder (n = 41), schizoaffective disorder (n = 6) or a previous postpartum psychosis (n = 4) and 61 healthy women with no past or current DSM-IV diagnosis and no family history of postpartum psychosis. Women were followed up from the third trimester of pregnancy to 4 weeks' post partum. Women at risk who had a psychiatric relapse in the first 4 weeks' post partum (AR-unwell) (n = 22), were compared with those at risk who remained well (AR-well) (n = 29) on measures of psychosocial stress (severe childhood maltreatment and stressful life events) and biological stress (cortisol and inflammatory biomarkers). Results: Logistic regression analyses revealed that severe childhood maltreatment ( OR  = 4.9, 95% CI 0.5–49.2) and higher daily cortisol in the third trimester of pregnancy ( OR =3.7, 95% CI 1.2–11.6) predicted psychiatric relapse in the first 4 weeks' post partum in women at risk of postpartum psychosis after adjusting for clinical and sociodemographic covariates. Conclusion: The current study provides evidence for the role of psychosocial stress and the biological stress system in the risk of postpartum relapse in women at risk of postpartum psychosis. Highlights: We compared women at risk of postpartum psychosis who relapsed with those who remained well and controls not at risk. Childhood maltreatment was associated with increased risk of postpartum relapse. Higher daily cortisol, but not inflammatory markers, in the third trimester of pregnancy predicted postpartum relapse. No association was found between stressful life events in pregnancy and postpartum relapse. Psychiatric relapse during pregnancy was associated with postpartum relapse.